Measure Theoretic Generalization of Pečarić, Mercer and Wu-Srivastava Results - Jakšetić, Julije; Pečarić, Josip; Smoljak Kalamir, Ksenija (Sarajevo Journal of Mathematics, 2024)
In this paper generalizations of Steffensen’s inequality obtained by Pečari´c, Mercer and Wu-Srivastava are further extended in a measure theoretic sense. Motivated by Wu and Srivastava’s refined and sharpened version of Mercer’s result related inequalities for positive Borel measures are obtained.